Role of Magnetic Resonance Imaging in Predicting Residual Breast Cancer After Vacuum-Assisted Breast Biopsy. Issue 6 (June 2021) - Zheng, Sun; Qi, Liu; Guang-Qiang, Zhang; Ming-Ming, Shi; Chun-Hong, Xu
Purpose: This study aims to evaluate the effectiveness of breast magnetic resonance imaging (MRI) in detecting residual breast cancer in patients after vacuum-assisted breast biopsy (VABB). Methods: Between 2012 and 2019, 26 patients with breast cancer who underwent VABB were enrolled. Breast MRI was conducted after VABB. Imaging findings were then compared with the histopathological results. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy were calculated. Results: Residual cancer was confirmed histologically in 8 of the 26 patients after VABB. The overall sensitivity, specificity, PPV, NPV, and accuracy of MRI for diagnosing residual cancer were 79.9%, 73.0%, 87.1%, 61.3%, and 77.8%, respectively. The sensitivity and NPV improved to 100%, when the number of biopsy specimens was larger than five. Conclusion: Breast MRI showed high sensitivity and NPV in detecting residual breast tumor after VABB.